2011
DOI: 10.1007/s11090-011-9314-3
|View full text |Cite
|
Sign up to set email alerts
|

DBD Surface Modification of Polymers in Relation to the Spatial Distribution of Reactive Oxygen Species

Abstract: The homogeneity of a helium dielectric barrier discharge, working at atmospheric pressure and containing oxygen as contaminant, is assessed by mapping the spatial distribution of oxygen metastable atoms in relation to the uniformity of surface properties. Tunable diode laser absorption spectroscopy is used to monitor the time evolution of the absorption coefficient corresponding to the oxygen metastable atoms on the 3 5 S 2 level, as a function of the laser absorbing path, whereas bi-dimensional Abel transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…An analysis reveals that the modification of the average surface roughness on the treated surfaces is minimal, typically only a few nanometers. This outcome is consistent with previous research on various polymers treated with different atmospheric-pressure DBD arrangements, where the maximum variation of Ram and Rrms was found to be around 3-6 nm [39]. In fact, a significant modification of the roughness could indicate surface degradation caused by the extended treatment.…”
Section: Afm Surface Morphology Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…An analysis reveals that the modification of the average surface roughness on the treated surfaces is minimal, typically only a few nanometers. This outcome is consistent with previous research on various polymers treated with different atmospheric-pressure DBD arrangements, where the maximum variation of Ram and Rrms was found to be around 3-6 nm [39]. In fact, a significant modification of the roughness could indicate surface degradation caused by the extended treatment.…”
Section: Afm Surface Morphology Analysissupporting
confidence: 92%
“…Interestingly, the evolution trend varies for different polymer structures. In the case of the three PEs and PP, an increase in surface roughness is observed, which is consistent with most studies [39]. However, for PS, the treated surface is smoother compared to the untreated one.…”
Section: Afm Surface Morphology Analysissupporting
confidence: 91%
“…While surface morphology was not examined in this study, previous research on various polymers treated with different atmospheric pressure DBD arrangements has demonstrated that changes in average surface roughness are minimal, typically only a few nanometers. Therefore, the influence of surface roughness on the measured contact angle is likely negligible [23,[44][45][46]. For PET and PEEK, hydrophobic recovery occurs predominantly within the first 2-3 days following plasma treatment, with minor subsequent changes.…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…By introducing a pulsed discharge between the successive RF discharge bursts in pulsed modulated RF discharges, the discharge is named as cascade discharge and the ignition of RF discharge is enhanced by pulsed discharge with reduced ignition time [13,14]. On the other hand, the uniformity of atmospheric glow discharge is not well addressed, especially along the electrode surface, which is an important issue in most applications [15,16].…”
Section: Introductionmentioning
confidence: 99%